Formation of the professional culture of future teachers-speech therapists through the use of innovative technologies - Savinova, Natalia; Berehova, Maria; Kuterzhynska, Kateryna (My University, 2022)
In the article the focus is on addressing the evolving landscape of education, specifically tailored to the training of future speech therapists. In this modern educational context, the article emphasizes the critical importance of cultivating professional, personal, and moral culture as integral components that encapsulate the positive socio-personal achievements within the field of pedagogy. The core objective of this research endeavor is to delineate the criteria, indicators, and diagnostic tasks necessary for the development of the professional culture of prospective speech therapists. Simultaneously, it seeks to assess the current state of professional culture formation among these aspiring educators. To achieve this goal, the authors employ diagnostic sections that serve as the foundation for establishing a comprehensive criterion-indicator framework for the nurturing of professional culture among future speech therapy teachers. One pivotal aspect under scrutiny is the culture of professional communication, which serves as an important gauge of proficiency in expressive speech. This proficiency extends to adhering to established Ukrainian language norms, encompassing orthoepic norms, lexical and grammatical conventions, intonation, and content richness. It further assesses the degree of erudition, general tolerance, and the conscious and respectful approach adopted by educators in their teaching practice.
Savinova N. Formation of the professional culture of future teachers-speech therapists through the use of innovative technologies / N. Savinova, M. Berehova, K. Kuterzhynska // ScienceRise: Pedagogical Education, 2022. – Vol. 4 (49). – P. 4–11
Keywords: Технології, інноваційно-технологічна компетентність, особистісна та професійна компетентність, професійна культура, вчитель-логопед; Technologies, innovative technologies, competence, personal and professional competence, professional culture, teacher-speech therapist